2020
DOI: 10.1007/s11071-020-06055-x
|View full text |Cite
|
Sign up to set email alerts
|

Friction-induced vibration considering multiple types of nonlinearities

Abstract: The friction-induced vibration of a novel 5-DoF (degree-of-freedom) mass-on-oscillating-belt model considering multiple types of nonlinearities is studied. The first type of nonlinearity in the system is the nonlinear contact stiffness, the second is the non-smooth behaviour including stick, slip and separation, and the third is the geometrical nonlinearity brought about by the moving-load feature of the mass slider on the rigid belt. Both the linear stability of the system and the nonlinear steady-state respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The gradually formed process means system has experienced stable to unstable change the change under the uncontrolled movement model caused by energy. Ouyang 41 studied the friction-induced vibration of a novel 5-DoF (degree-of-freedom) mass-on-oscillating-belt model considering multiple types of nonlinearities. He found that the steady-state response of the system was related to the bifurcation behavior of some parameters, which means each type of nonlinearity has significant effect on the linear stability and nonlinear steady-state responses of the system.…”
Section: Stick-slip Vibration Analysismentioning
confidence: 99%
“…The gradually formed process means system has experienced stable to unstable change the change under the uncontrolled movement model caused by energy. Ouyang 41 studied the friction-induced vibration of a novel 5-DoF (degree-of-freedom) mass-on-oscillating-belt model considering multiple types of nonlinearities. He found that the steady-state response of the system was related to the bifurcation behavior of some parameters, which means each type of nonlinearity has significant effect on the linear stability and nonlinear steady-state responses of the system.…”
Section: Stick-slip Vibration Analysismentioning
confidence: 99%
“…Furthermore, the linear stability analysis approach on the investigation of squeal behavior was found to be misleading in some studies (Liu and Ouyang, 2020;Sinou, 2010;Zhang et al, 2016). Liu and Ouyang studied the dynamics of a disc brake system with a five degree of freedom mathematical model by numerical and analytical means.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Ouyang studied the dynamics of a disc brake system with a five degree of freedom mathematical model by numerical and analytical means. The authors included the effects due to contact stiffness, stick-slip and geometrical nonlinearities in their model and concluded that a nonlinear stability analysis was crucial for detection of squeal instability (Liu and Ouyang, 2020). Sinou claimed that the stability analysis performed on the linearized system provided limited information about dynamic behavior of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Complex eigenvalue analysis (CEA) and transient dynamic analysis (TDA) are effective techniques for studying friction-induced vibration problems [24]. CEA, used in applications such as aeroelastic flutter [25] and brake squeal analysis [26], involves finding the equilibrium of the nonlinear system and linearising the system equations near this point to derive the stiffness and damping matrices.…”
Section: Introductionmentioning
confidence: 99%
“…CEA is widely used in industry due to its computational efficiency and its ability to quickly identify unstable modes [27]. TDA, on the other hand, provides a detailed time response of the system's dynamic behaviour, including stick-slip effects and bifurcation [28,24].…”
Section: Introductionmentioning
confidence: 99%